Elevated soluble CD23 level indicates increased risk of B cell non-Hodgkin’s lymphomas: evidence from a meta-analysis - Huang, Yi-shu; Zhou, Xiang; Yang, Zhi-fang (Annals of hematology, 2018)
The aim of the present study was to determine whether circulating soluble CD23 (sCD23) was associated with B cells non-Hodgkin’s lymphomas (B-NHL). PubMed, EMBASE, and ISI Web of Science were extensively searched without language restriction. Data was extracted in a standardized data collection sheet after two reviewers scanned studies independently. The association between sCD23 and NHL was indicated as odds ratio (OR) along with its related 95% confidence interval (95% CI). Meta-analysis was conducted via RevMan 5.3. A total of five studies, which included 964 B-NHL patients and 1243 matched controls without B-NHL, among which 257 were HIV-positive donors and 986 were general controls, were included in our study. Meta-analysis revealed a significant association between peripheral sCD23 level and B-NHL in HIV-positive samples (OR 1.66, 95% CI 1.25, 2.20; P = 0.0005) as well as the general population (OR 2.51; 95% CI 1.71, 3.86; P < 0.00001). Meta-analysis, stratified by sampling time prior to diagnosis, indicated potential HIV-NHL patients are 2.34-folds more likely to have higher blood sCD23 level, although this association is statistically meaningful only during 3-5 years prior to diagnosis (95% CI 1.27, 4.33). Subgroup analysis based on B-NHL type demonstrated a significant association between sCD23 level and diffuse large B cell lymphoma (DLBCL), chronic lymphocytic leukemia (CLL), and follicular lymphoma (FL). The findings of our study indicate a positive association of circulating sCD23 level and B-NHL risks and highlight the possibility of sCD23 as a predictive marker of B-NHL. However, to better understand the underlying mechanism, further studies are needed.
Gesehen am 10.10.2019
Im Titel ist die Zahl "23" tiefer gestellt